Northwest History. Alaska. Dogs, Dog Races & Mushers. (1936)
Wee Lady Mushes 1000-Mile Jaunt. WEE LADY MUSHES 1000-Mile Jaunt By Associated Press. SKAGWAY, Alaska, Jan. 28.—Mary Joyce, small but venturesome proprietress of a Taku river hunting lodge, traveled alone, but for her sled dogs, today on the snowy trail between Whitehorse and Kluane lake, Yukon territory, second major leg in her 1000-mile journey from Juneau to Fairbanks. She left Whitehorse Sunday after resting from a speedy 225-mile trip through deep snows and over treacherous ice from her home at Twin Glaciers via Tulsequah and Atlin, B. C. She is carrying cameras, film and a letter from Territorial Governor John W. Troy to Fairbanks' mayor, E. C. Collins. Roads end at Kluane lake, but Miss Joyce said she planned to hire an Indian guide there to accompany her across the almost unmapped wilderness 250 miles to Tanana crossing, Alaska. There is a scanty network of pack trails between the lake and the Tanana river, down which she will mush to Fairbanks, but only a few villages, and they are far off her course.